Utilization of School Plants and Effective Teaching and Learning in a Contemporary Society - Nkeiru, Nwamara Ezinne; Rose, Igwe Uzoamaka (International Journal of Contemporary Studies in Education, 2023)
The study investigated utilization of school plants and effective teaching and learning in a contemporary society. Two objectives, two research questions and two hypotheses guided the study. A correlational research method was employed in carrying out the study. The population of the study comprised of six thousand eight hundred and ninety-three (6,893) teachers from all the 286 public senior secondary schools in Rivers State. The stratified random sampling technique was used to select seven hundred (700) teachers from ten (10) schools in 12 out of the 23 local government areas representing 10% of the population. The instrument for this study was a questionnaire which was divided into two sections titled “Utilization of School Plants Questionnaire (USPQ)” and “Utilization of School Plant and Effective Teaching and Learning (USPETL)”. Pearson Product Moment Correlation Coefficient was used to obtain the reliability of 0.81.  Mean and standard deviation were used to answer the research questions while Pearson Product Moment Correlation was used to test the hypothesis at 0.05% confidence level. The findings revealed that there is a significant relationship between utilization of school plants and effective teaching and learning. The study therefore concluded that utilization of school plants by teachers for effective teaching and learning, increases students’ level of assimilation and contribute greatly to the achievement of educational goals in a contemporary society. It was recommended among others that the government should improve innovations of the school buildings and laboratory equipment to meet the needs of a contemporary society.